Humanism and the Urban Spaces in Meja Mwangi’s Novels - Martha Flavian, Ombati, (International Journal of Scientific Research and Management (IJSRM), 2022)
Humanism is a conscious awareness and reciprocal actions of being humane. An individual’s efforts to be humane and to realize fully their own humanity is affected by the forces within and outside him or her. One of the roles of literature is to toy with this question of humanism, to describe its condition and how individuals strive to realize and exercise their humanity. This paper examines humanism and the urban environment as depicted in the selected novels of Kenya’s popular novelist, Meja Mwangi. To this end, Meja Mwangi’s popular fiction, Kill Me Quick (1973), Going Down River Road (1976) and The Cockroach Dance (1979) was critiqued in researching this question, given that literature reflects reality. The texts are Mwangi’s urban trilogy, among his forty-six novels. The study was qualitative in approach, employing analytical research design in the collection and analysis of data. The gathered data was analysed through content analysis. The study population comprised Kenyan popular fiction, with a special focus on novels by Meja Mwangi. The study further focused on Mwangi’s novels that are forty-six in number. Purposive sampling technique was employed with the inclusion criterion being Mwangi’s novels that address the humanistic issues being investigated. The sampled texts were Mwangi’s three urban-based novels mentioned above. The data was collected through close textual reading. Data collected was categorised along with the study’s units of analysis, namely Mwangi’s thematic concerns on humanism, characterisation, and narrative techniques. From the findings, a close reading of Kill Me Quick, Going Down River Road and The Cockroach Dance unravel instances and encounters with characters entangled in twists of fate in an urban locale. This is revealed through their actions, utterances and behaviour. It is also evident that the trilogy, particularly Kill Me Quick chronicles both rural and urban environments, whereas the other two centre on an urban locale. However, many issues have been raised in these novels about the urban space with its dislocation of individuals’ humane dispositions as their moral and cultural values gradually wane.